Rhythmic radial oxygen loss enhances soil phosphorus bioavailability - Cai Li; Hu Sheng; Mengxi Tan; Hengyi Dai; Xiaolong Wang; Huacheng Xu; Shiming Ding; Guoqiang Zhao (Nature Communications)
Abstract Phosphorus (P) availability is vital for global primary productivity, yet it is often immobilized in soils by redox-inert crystalline iron (oxy)hydroxides. Here we show that diel radial oxygen loss (ROL) from plant roots induces redox fluctuations in the rhizosphere, activating these iron minerals and enhancing P mobilization. Nighttime reduction and daytime oxidation drive the formation of reactive metastable iron phases (RMPs) on root surfaces, forming a redox-active iron plaque. These RMPs undergo rapid dissolution–reformation cycles, facilitating P transfer from soil to porewater for plant uptake. Using multiple aquatic plants from agriculturally developed regions, we demonstrate that ROL broadly enhances soil P availability. In rice paddies, ROL-activated P release accounts for 8.7% of global P fertilizer input, contributing an estimated economic value of USD 0.52 billion annually. Our findings uncover a previously overlooked redox mechanism by which plants enhance P acquisition, with broad implications for nutrient cycling and agricultural sustainability.